The force of HER2 – A druggable target in NSCLC?. (June 2020) - Jebbink, M.; de Langen, A.J.; Boelens, M.C.; Monkhorst, K.; Smit, E.F.
Highlights: Three principal mechanisms of HER2 alterations can be identified: protein overexpression, gene amplification and gene mutations. No consensus about HER2 subgroup definitions has been obtained, complicating the interpretation of the results of the many trials studying possible treatment strategies. Future research should focus on the definition of HER2 alteration subgroups and test therapeutic agents in these different subgroups. Abstract: Since several years targeted therapy has been part of treatment in NSCLC in subsets of patients with specific genetic alterations. One of these alterations involves HER2, a member of the ERBB family of tyrosine kinase receptors. Despite that HER2 alterations in NSCLC have been studied for years, there is still no consensus about subgroup definitions. In this review HER2 alterations in NSCLC are discussed, including diagnostic challenges and treatment strategies. Three principal mechanisms of HER2 alterations can be identified: HER2 protein overexpression, HER2 gene amplification and HER2 gene mutations. There are several methods for the detection of HER2 "positivity" in NSCLC, but no gold standard has been established. Laboratory methods for assessment of HER2 positivity in NSCLC include immunohistochemistry (IHC) for protein overexpression and fluorescent in situ hybridization (FISH) and next generation sequencing (NGS) for genetic alterations. Many trials testing HER2 targeted therapy in HER2 altered NSCLC has not lead to a renewed standard of care for this group of patients. Therefore, today the (re)search on how to analyse, define and treat HER2 alterations in NSCLC continues. Still there is no consensus about HER2 subgroup definitions and results of the many trials studying possible treatment strategies are inconclusive. Future research should focus on the most important missing link, whether all HER2 alterations are relevant oncogenic drivers and whether it should be considered as a therapeutic target in NSCLC.